Citizenship, epistemic violence and subjectivity - Martin Savransky (Revista CIDOB d'Afers Internacionals, 2011)
In the contemporary debate on the issue of citizenship within Europe, one can observe a long tradition that conceives of it only as the product of a legal-political process for the concession of political entitlements and thus, as part of the exercise of sovereign power. This text places its main focus of interest on the epistemic and regulatory dimension of such political provisions, and on the challenges to the distinction between citizen and non-citizen posed by a focus on practices and performances of citizenship. By means of a critical epistemic reflection, the article questions the frames of representation through which both citizenship and political subjectivities are regulated. It is argued that only by beginning to pay attention not only to the concession but to the practice of citizenship, its confrontational performances and its relationship to questions of power and subjectivity that we may attend to the complexity of the processes involved.